Quantitative evaluation of the subsequent hemorrhage with arteriography-derived hemodynamic features in patients with untreated cerebral arteriovenous malformation - Zhu, Haoyu; Liu, Lian; Chang, Yuzhou; Song, Yuqi; Liang, Shikai; Ma, Chao; Zhang, Longhui; Liang, Fei; Jiang, Chuhan; Zhang, Yupeng (Frontiers in Neurology, 2023)
Background Patients with untreated cerebral arteriovenous malformations (AVMs) are at risk of intracerebral hemorrhage. However, treatment to prevent AVM hemorrhage carries risks. Objective This study aimed to analyze the AVM nidus-related hemodynamic features and identify the risk factors for subsequent hemorrhage. Methods We retrospectively identified patients with untreated AVMs who were assessed at our institution between March 2010 and March 2021. Patients with ≥6 months of treatment-free and hemorrhage-free follow-up after diagnosed by digital subtraction angiography were included in subsequent examinations. The hemodynamic features were extracted from five contrast flow-related parameter maps. The Kaplan-Meier analyses and Cox proportional hazards regression models were used to find the potential risk factors for subsequent hemorrhage. Results Overall, 104 patients with a mean follow-up duration of 3.37 years (median, 2.42 years; range, 6–117 months) were included in study, and the annual risk of rupture was 3.7%. Previous rupture (hazard ratio [HR], 4.89; 95% confidence interval [CI], 1.16–20.72), deep AVM location (HR, 4.02; 95% CI, 1.01–15.99), higher cerebral blood volume (HR, 3.35; 95% CI, 1.15–9.74) in the nidus, and higher stasis index (HR, 1.54; 95% CI, 1.06–2.24) in the nidus were associated with subsequent hemorrhage in untreated AVMs. Conclusion Higher cerebral blood volume and stasis index in the nidus suggest increased blood inflow and stagnant blood drainage. The combination of these factors may cause subsequent hemorrhage of AVMs.